The "Due Dilligence" Standard in Labour Law - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
One of the positive innovations in the field of labour law is the introduction of the "due diligence" standard. Altough this principle has long been known and applied in other areas of law, it is new in labour law. The global application of due diligence standard, found in UN, ILO, OECD documents, and soon in the EU directive, as well as in many national laws, should lead to better and more comprehensive protection of the human rights of employees, as well as of all other persons regarding that work. This paper discusses more about the meaning, development and application of due diligence standards in the context of employee rights.
Keywords: due diligence, human rights, labour relations